1999
DOI: 10.1103/physrevlett.83.1018
|View full text |Cite
|
Sign up to set email alerts
|

Predominantly Superconducting Origin of Large Energy Gaps in UnderdopedBi2Sr2CaCu

Abstract: New tunneling data are reported in Bi 2 Sr 2 CaCu 2 O 81d which show quasiparticle excitation gaps, D, reaching values as high as 60 meV for underdoped crystals with T c 70 K. These energy gaps are nearly 3 times larger than those of overdoped crystals with similar T c . Despite the large differences in gap magnitude, the tunneling spectra display qualitatively similar characteristics over the entire doping range. Detailed examination of the spectra, including the Josephson I c R n product measured in break ju… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

37
200
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(241 citation statements)
references
References 20 publications
37
200
4
Order By: Relevance
“…In Bi-2212, the spectral "dip/hump" features were widely observed [14][15][16][17][18][19] and attributed to quasiparticle damping via interactions with collective spin fluctuations [27,28]. In the strong coupling limit, the spectral dip is expected to appear at the energy v dip D 1 V res , where D is the measured gap, and V res is associated with the resonance of collective spin excitations [27,28].…”
Section: P H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 99%
See 3 more Smart Citations
“…In Bi-2212, the spectral "dip/hump" features were widely observed [14][15][16][17][18][19] and attributed to quasiparticle damping via interactions with collective spin fluctuations [27,28]. In the strong coupling limit, the spectral dip is expected to appear at the energy v dip D 1 V res , where D is the measured gap, and V res is associated with the resonance of collective spin excitations [27,28].…”
Section: P H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 99%
“…Assuming the position where a local maximum intensity of a resonant peak occurred as an impurity site, we found that the peak persisted over several lattice constants for displacement along either ͕100͖ or K ra sn o v e t a l . 20 M iya ka w a e t a l. 14,15 R e n n e r e t a l . ͕010͖, and the peak intensity decreased rapidly within the Fermi wavelength, as shown in the inset of Fig.…”
Section: P H Y S I C a L R E V I E W L E T T E R Smentioning
confidence: 99%
See 2 more Smart Citations
“…Spectrally l must be related to the hump-feature. Eventually it remains preserved for T > T c (insert in Fig.1) at the dopings where T c is optimized [52] and it is shifted to larger energies with reduced doping [54]. The common manifestation of two underdoped state pseudogaps is expected theoretically.…”
Section: Illustration and Discussionmentioning
confidence: 75%